Right to privacy, Big Data and data protection: new challenges of the Colombian legal system - Dayron Dannylo Reyes Quintero; Margarita Rosa Lobo Contreras; Lucía Dayana Amaya Barbosa (Postulados: Revista Sociojurídica)
This research work analyzes the challenges of the Colombian legal system in the face of Big Data and the processing of personal data in the digital age, in relation to the right to privacy. This includes challenges in the implementation of data management, artificial intelligence and regulation within the social, business, political and other areas in what we understand as the globalization process. For this, the present study mentions the means by which people can assert their rights regarding the protection of their data, remembering the importance and observing Habeas Data as a constitutional action that covers the contentious judicial process aimed at safeguarding the data. personal. Also, the perception and characteristics of Big Data are disclosed, trying to know how the rights involved in the materialization of the data analysis process can be protected; Finally, a critical sense is applied to the use of Big Data in modern political platforms, understanding the panorama for the Colombian legal system, which brings with it the probable violation of fundamental rights, such as personal privacy.